1991
DOI: 10.1016/0022-460x(91)90592-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-periodic motion caused by grazing incidence in an impact oscillator

Abstract: The motion of a single-degree-of-freedom, periodically forced oscillator subjected to a rigid amplitude constraint is considered. Using analytical methods, the singularities caused by grazing impact are studied. It is shown that as a stable periodic orbit comes to grazing impact under the control of a single parameter, a special type of bifurcation occurs. The motion after the bifurcation may be non-periodic, and a criterion for this based on orientation and eigenvalues is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
434
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 704 publications
(438 citation statements)
references
References 8 publications
(13 reference statements)
3
434
0
1
Order By: Relevance
“…Such complex dynamics can arise either through smooth bifurcations, in particular period-doubling bifurcations, or through grazing bifurcations which arise when u has a grazing impact with z with du/dt = dv/dt. Grazing leads to large local stretching of phase space and is described in detail in [9,26,27]. Fig.…”
Section: Review Of the Single Particle Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Such complex dynamics can arise either through smooth bifurcations, in particular period-doubling bifurcations, or through grazing bifurcations which arise when u has a grazing impact with z with du/dt = dv/dt. Grazing leads to large local stretching of phase space and is described in detail in [9,26,27]. Fig.…”
Section: Review Of the Single Particle Systemmentioning
confidence: 99%
“…In contrast, the transition as we cross Σ 2 is a grazing event [12,28,29,17], involving a grazing impact between z and u close to t 0 . A more refined analysis (see for example [26]) of the grazing event shows that this has a square-root form. The discontinuous map is an outer approximation to this.…”
Section: Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…X max is the tip amplitude at the steady-state. For the grazing impact, the Poincaré mapping can be analytically derived [3,23]. Therefore, the bifurcation and the transition to chaos can be clearly shown [3].…”
Section: Resultsmentioning
confidence: 99%
“…van de Water and Molenaar [3] demonstrated that for the grazing impact, the tapping-mode AFM displays the characteristic features of an impact oscillator. However, the grazing impact is a particular impact case with zero impact velocity [22,23]. The AFM studied by van de Water and Molenaar interacts with the rigid surface through a liquid bridge, which offers a mechanism to realize the grazing impact [3].…”
Section: Introductionmentioning
confidence: 99%